A randomized comparative study of epidural ropivacaine 0.2% with adjuvant fentanyl or nalbuphine for post-operative analgesia in lower limb surgeries - Harichandan, Anup Kumar; Khuntia, Manaswini; Sahu, Bimal Prasad; Dash, Sourav; Biswal, Debadas; Dalai, Harikrishna; Jena, Shibanee (Asian Journal of Medical Sciences, 2024)
Background: Opioid analgesics with local anesthetics in an epidural route are extremely safe, effective, and reliable methods of post-operative pain relief. Aims and Objectives: The primary objective is to compare the duration of analgesia and pain scoring by visual analog scale. The secondary objective is to monitor sedation, hemodynamic changes, and side effects such as nausea, vomiting, shivering, and pruritus. Materials and Methods: A prospective randomized comparative study of 0.2% ropivacaine with nalbuphine and 0.2% ropivacaine with fentanyl in epidural route for post-operative analgesia in elective lower limb surgeries under spinal anesthesia was carried out in a population of 80 patients. After 1½ h of surgery under spinal anesthesia, patients in group RF received 10 mL of 0.2% ropivacaine with 25 mcg of fentanyl and those in group RN received 10 mL of 0.2% ropivacaine with 2.5 mg of nalbuphine and were observed for the study parameters over time. Results: The mean duration of analgesia was longer in group RN than in group RF (398.45 vs. 222.88 min). The hemodynamic parameters such as heart rate, mean arterial pressure, and respiratory rate were statistically significant from 240 to 480 min which is 4–6 h in group RF and 6–8 h in group RN. 27.5% of patients in group RN attained sedation whereas 7.5% of subjects in group RF had a sedation score of 2 and above at 30 min. The subjects in group RN had a lower visual analog score than group RF. 12% and 4% of patients had vomiting in group RN and group RF, respectively. Conclusion: Epidural nalbuphine in a dose of 2.5 mg with 0.2% ropivacaine provided a longer duration of analgesia with better pain score and more sedation which was advantageous for post-operative patient compliance and satisfaction as compared to 25 mcg of fentanyl with 0.2% ropivacaine.